Izuzeća za vozače i vozila - posebice u odnosu na prijevoz putnika na linijskim vožnjama na udaljenosti do 50 kilometara - Gočin, Miljenko (Array, 2018)
Exemptions from the application of certain provisions on working time, obligatory breaks for mobile workers and recording equipment in road transport applies to certain drivers who operate the excluded categories of vehicles and to vehicles which are partially or entirely exempted from the obligation to install a road vehicle recording device – a tachograph. Through this research, this paper answers the question what exactly the exemptions are, what law sources appertain to these exceptions, whether they apply in practice and what the novelties are in their practical implementation. The paper also explains the legal rules that determine the working hours and obligatory breaks of excluded drivers and how to keep records for such workers and their working hours. At the end of the paper, authors indicate advantages and disadvantages of applying these exemptions for both drivers and employers, and provide a concluding assessment of the benefits of these exemptions, as well as the need for additional interventions through acts, but even more, through practical knowledge of the rights and obligations of drivers and employers in order to overcome the vagueness and insecurities of these major participants in the transport of goods and passengers in road transport.